Stair-descent phenotypes in community-dwelling older adults determined using high-level balance tasks. - Tanaka, Takahiro; Hase, Kimitaka; Mori, Kimihiko; Wakida, Masanori; Arima, Yasuaki; Kubo, Takanari; Taguchi, Meguru (Aging Clinical & Experimental Research, 2025)
Background: Falls on stairs are a major cause of severe injuries among older adults, with stair descent posing significantly greater risks than ascent. Variations in stair descent phenotypes may reflect differences in physical function and biomechanical stability, and their identification may prevent falls. Aims: This study aims to classify stair descent phenotypes in older adults and investigate the biomechanical and physical functional differences between these phenotypes using hierarchical cluster analysis. Methods: Eighty-two older adults participated in this study. Stair descent was measured using a three-dimensional motion analysis system. Physical function was assessed using measures of muscle strength, walking speed, the Timed Up and Go Test (TUG), and the Community Balance and Mobility Scale (CB&M). Results: Hierarchical cluster analysis was performed on kinematic data obtained during stair descent. Three phenotypes were identified: neutral (N-type; 24%), extension (E-type; 52%), and rotation (R-type; 23%). There were no significant differences in lower limb muscle strength or walking speed among the different types, and TUG scores showed no differences in terms of mobility or balance abilities. However, CB&M scores were significantly lower for E-type and R-type compared to N-type. Sub-analyses revealed that while there were no differences in the mobility factor of CB&M between E-type and R-type, the strength factors were significantly lower compared to those for N-type. Discussion: These results suggest that E-type and R-type stair-descent patterns may be influenced by declines in standing balance ability and muscle strength. Conclusions: These findings may inform fall-prevention training programs related to stair descent among older adults.